The celebration: Every family has a secret. - Vinterberg, Thomas 1969- (DVD Video, 2004)
The Celebration is a Danish film, made by director Thomas Vinterberg, in 1998, which centres around the gathering of an upper class family for the 60th birthday celebrations of its patriarch, Helge Klingenfeldt-Hansen (Henning Moritzen) Ð soon after the mysterious death of his daughter, Linda. But what initially appears as a stuffy formal occasion begins to fragment, as dark family secrets come crawling out of the woodwork. At the birthday dinner, Christian, the eldest son of Helge, publicly accuses his father of sexually abusing and raping both him and his twin sister, Linda. Although, the other family members do not believe the accusations at first, at the end of the film, ChristianÕs accusations are confirmed when the younger sister, Helene, reads LindaÕs suicide note, which states she had begun to have dreams in which her father had begun to molest her again, which led to her suicide.